A Review on Medicinal Properties of Saffron toward Major Diseases. Issue 2 (3rd April 2017) - Razak, Saiful Izwan Abd; Anwar Hamzah, Mohd Syahir; Yee, Foong Choi; Kadir, Mohammed Rafiq Abdul; Nayan, Nadirul Hasraf Mat
ABSTRACT: The stigma of Crocus sativus, known as saffron, is one of the most expensive spices in the world. The bioactive components in saffron, picrocrocin, crocin, and safranal, have demonstrated a wide range of uses and capabilities in the medical field. This review is focused on the potential therapeutic applications of saffron on diabetes mellitus (DM), antitumor, anticancer, antidepressant, Alzheimer's disease (AD), cardiovascular disease (CVD), erectile dysfunction and antibacterial effects.